2014
DOI: 10.1016/j.acalib.2014.04.007
|View full text |Cite
|
Sign up to set email alerts
|

A Library and the Disciplines: A Collaborative Project Assessing the Impact of eBooks and Mobile Devices on Student Learning

Abstract: With the proliferation of technology usage, it is essential to understand the effect of implementation of technology in the academic setting. Specifically, this article examines the impact of eBooks and mobile devices on student learning. A pilot study was conducted with three areas of interest. The first question of interest found that owning or having access to two or more mobile devices significantly increased respondents' frequency of accessing eBooks. The second question examined the pros and cons of usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(15 citation statements)
references
References 18 publications
(15 reference statements)
1
11
0
2
Order By: Relevance
“…Glackin et al [18] reported that using ebook in teaching significantly affects students' learning experience and improve literacy skill. Felvégi and Matthew [19] and Ebner and Prettenthaler [20] stated that using ebook with hypermedia components can improve students' potential behavior in learning. Moreover, a study by Kör et al [21] shows that instructional materials in the form of PDF and video are used more often than animation and simulation.…”
Section: Resultsmentioning
confidence: 99%
“…Glackin et al [18] reported that using ebook in teaching significantly affects students' learning experience and improve literacy skill. Felvégi and Matthew [19] and Ebner and Prettenthaler [20] stated that using ebook with hypermedia components can improve students' potential behavior in learning. Moreover, a study by Kör et al [21] shows that instructional materials in the form of PDF and video are used more often than animation and simulation.…”
Section: Resultsmentioning
confidence: 99%
“…Mobile devices will increase in usage in medical education and health care. Glackin et al found that owning or having access to two or more mobile devices significantly increased respondents' frequency of accessing e-books and observed that e-books and mobile device use in the classroom will have a significant impact on the student's educational experience (9).…”
Section: Discussionmentioning
confidence: 99%
“…In [37], the authors attempted to address the effects of mobile devices and eBooks on student learning. Three questions were involved within the study.…”
Section: Ebooksmentioning
confidence: 99%